Dysfunction of HPV16-specific CD8+ T cells derived from oropharyngeal tumors is related to the expression of Tim-3 but not PD-1 - Hladíková, Kamila; Partlová, Simona; Koucký, Vladimír; Bouček, Jan; Fonteneau, Jean-Francois; Zábrodský, Michal; Tachezy, Ruth; Grega, Marek; Špíšek, Radek; Fialová, Anna (Oral oncology, 2018)
BACKGROUND: Human papillomavirus (HPV) type 16 infection is one of the most important etiological agents of oropharyngeal squamous cell carcinoma. Patients with HPV-associated carcinomas of the head and neck were reported to have a better clinical outcome than patients with HPV-negative tumors. Because HPV16 E6 and E7 oncoproteins are highly immunogenic and constitutively expressed, HPV-specific T cell immunity may play the key role in improving the prognosis of these patients. METHODS: Tumor-derived T cells were expanded in high levels of IL-2 and stimulated with HPV16 E6/E7 peptides in the presence or absence of anti-PD-1 monoclonal antibody nivolumab and soluble Tim-3. RESULTS: HPV16-specific tumor-infiltrating T cells were present in 73.1% of HPV-associated oropharyngeal tumors. HPV16 specific CD8+ TILs were able to produce IFNγ upon specific stimulation and predominantly expressed PD-1 but not Tim-3. Specific IFNγ production was further enhanced after a blockade of both PD-1 and Tim-3 pathways but not after a PD-1 blockade alone. Additionally, the specific stimulation of anti-HPV16 CD8+ T cells suppressed Tim-3 upregulation after the PD-1 blockade. CONCLUSION: Our data provide the rationale for combination cancer immunotherapy approaches, including the dual blockade of PD-1 and Tim-3 and, potentially, the use of HPV16-directed therapeutic vaccines.
Keywords: lidský papilomavirus 16; CD8-pozitivní T-lymfocyty; lidé; Adult; Middle Aged; PD-1; antigeny CD279; CD8-Positive T-Lymphocytes; Tumor Escape; Female; cytokiny; Lymphocytes, Tumor-Infiltrating; Humans; buněčný receptor 2 viru hepatitidy A; nivolumab; Tumor-infiltrating lymphocytes; Cytokines; lidé středního věku; mužské pohlaví; tumor infiltrující lymfocyty; protinádorové látky imunologicky aktivní; nádory orofaryngu; Human papillomavirus; Oropharyngeal cancer; Antineoplastic Agents, Immunological; ženské pohlaví; Human papillomavirus 16; Programmed Cell Death 1 Receptor; únik nádoru z imunitní kontroly; Hepatitis A Virus Cellular Receptor 2; Male; Aged; Oropharyngeal Neoplasms; Nivolumab; Tim-3; dospělí; senioři